Hubungan Pengetahuan dan Sikap Dalam Upaya Pencegahan Komplikasi Hipertensi Pada Lansia - Sari, Nela Novita (Yayasan Jompa Research and Development, 2024)
The prevalence of hypertension worldwide is estimated to be around 1.28 billion. The prevalence of hypertension in Indonesia based on the results of measurements in the 18-year-old population is 34.1%. While in Pariaman City in 2023 the number of people with hypertension was recorded at 8,599 people. Judging from the number of sufferers, the Air Santok Health Center working area has a high incidence of hypertension, where in 2022 the incidence of hypertension was recorded at 749 cases and increased to 809 cases in 2023. The purpose of the study was to determine the relationship between knowledge and attitudes in efforts to prevent complications of hypertension in the elderly in the working area of the Air Santok Health Center, Pariaman City. This research is a type of quantitative research with an analytic descriptive design with a cross sectional approach. The population of people suffering from hypertension who visited the Air Santok health center was 809 people with a sample of 89 people. The results of the study found that 56.2% had low knowledge. 55.1% have a negative attitude. 53.9% are not good at preventing hypertension. There is a significant relationship between knowledge and prevention of hypertension complications, with a p value obtained of 0.000. There is a significant relationship between attitude and prevention of hypertension complications, with a p value of 0.000.